2003
DOI: 10.1046/j.1365-8711.2003.06527.x
|View full text |Cite
|
Sign up to set email alerts
|

The 2dF QSO Redshift Survey -- XI. The QSO power spectrum

Abstract: We present a power spectrum analysis of the final 2dF Quasi-Stellar Object (QSO) Redshift Survey catalogue containing 22 652 QSOs. Utilizing the huge volume probed by the QSOs, we can accurately measure power out to scales of ∼500 h −1 Mpc and derive new constraints, at z ∼ 1.4, on the matter and baryonic contents of the Universe. Importantly, these new cosmological constraints are derived at an intermediate epoch between the cosmic microwave background observations at z ∼ 1000, and local (z ∼ 0) studies of la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The space density of detected quasars may still be too low, however, for these plots to show structure; if the 22,600 quasars extend to redshifts near z ¼ 3 and the 205,000 galaxies plotted by Tegmark et al (2004) extend only to z ¼ 0:2, the galaxy/quasar number density ratio per unit volume between these two samples is huge ($8000/1). Although it is true that the QSO power spectrum results of Outram et al (2003) agreed with galaxy results, it is not clear that the discrete features in the redshift distribution that we are discussing here could not have influenced the result. Furthermore, it is difficult to prove that the DIR model would not also give acceptable results since the redshift distribution would be completely new, and only by repeating the analysis using the new distance redshifts of the DIR model could this be determined.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The space density of detected quasars may still be too low, however, for these plots to show structure; if the 22,600 quasars extend to redshifts near z ¼ 3 and the 205,000 galaxies plotted by Tegmark et al (2004) extend only to z ¼ 0:2, the galaxy/quasar number density ratio per unit volume between these two samples is huge ($8000/1). Although it is true that the QSO power spectrum results of Outram et al (2003) agreed with galaxy results, it is not clear that the discrete features in the redshift distribution that we are discussing here could not have influenced the result. Furthermore, it is difficult to prove that the DIR model would not also give acceptable results since the redshift distribution would be completely new, and only by repeating the analysis using the new distance redshifts of the DIR model could this be determined.…”
Section: Discussionmentioning
confidence: 59%
“…An analysis of the QSO power spectrum of 22,652 QSOs in the Two-Degree Field (2dF) QSO Redshift Survey catalog has been presented by Outram et al (2003), who found, assuming cosmological redshifts, that the amplitude of clustering of QSOs at a mean redshift of z ¼ 1:4 is similar to that of present-day galaxies. A comparison of the power spectra of QSOs at low and high redshift also showed little evidence for any evolution in the amplitude.…”
Section: Discussionmentioning
confidence: 99%
“…A real spectrum cannot have an infinitely sharp peak, which should be smoothed by some damping effects. Recent observations have indicated that the measured P(k) has a rather flat peak with large systematic errors on large scales (Outram et al 2003;Padilla & Baugh 2003;Tegmark et al 2004;Maller et al 2005;Percival 2005). …”
Section: Power Spectrummentioning
confidence: 99%
“…Quasar redshift surveys have often operated in tandem with galaxy surveys, and have highlighted the possibility of using quasars to constrain cosmology at higher redshifts than would be possible for galaxy samples to similar magnitude limits [e.g. [38][39][40].…”
Section: Introductionmentioning
confidence: 99%